“Se são consumidores, por que não estudá-los?”: o marketing islâmico e o perfil do consumidor muçulmano no Brasil - Jefferson Oliveira da Silva Lacerda (2018)
According to data of the last Demographic Census, in Brazil, the Islamic community has presented a growth of approximately 30% of the number of Muslims. For Brazilian Islamic institutions today the number of followers exceeds 1 million faithful (RIBEIRO, 2012, CARDOSO, 2015). Such individuals have as a rule of faith and practice the writings of the Qur'an, which presents the principles of religion and among these obligations is the consumption of halal products. Knowing this, the present quantitative bias thesis has as main objective to evaluate the correlation between the Islamic religiosity and the consumption of halal products, as well as to outline the profile of the Muslim consumer in Brazil. For this, a scale measuring these constructs was developed and validated, and for that, the steps presented by Costa (2011) were followed. The scale was applied in two moments, the first sample being applied with 206 Muslims and the second sample with 260. Regarding the level of reliability (Cronbach's alpha), the scale presented a value considered statistically satisfactory, that is, α = 0,86. Thus, nine dimensions of analysis were obtained through the average ranking, showing the level of agreement of the items present in the construct, as well as the correlation between Islamic religiosity and consumption.